A translator's handbook on the Gospel of Mark - Bratcher, Robert G.; Nida, Eugene Albert, 1914- (Leiden, The Netherlands Brill, 1961)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Mark -- study and teaching